Análise e projeto de antenas patch de microfita com substrato inspirado em arranjo EBG - Andrade, Betoven Oliveira de (2019)
After decades of the first publications on microstrip antennas, research and applications continue to expand. This is the consequence of several of its attractive features, especially the possibility of mounting in the same plane of the transceiver circuits. It turns out that this advantage causes some problems, for example, the waves produced by the circuits reflect and refract inside the substrate, since it has different refractive indexes, which causes surface currents in the earth plane, leading to a bandwidth narrower and also at lower radiation efficiency and low gain, since some of the energy is wasted. To solve such undesirable characteristics, several techniques have been investigated and employed, one of the most promising being the use of Electromagnetic Band-Gap (EBG) substrates. The EBG materials are periodic structures in a dielectric or conductive material. They propagate the electromagnetic waves at a frequency specific to all states of polarization and angles of incidence, offering pass-band and stop-band characteristics. Studies of new structures, techniques and equations for EBG materials in the form of periodic holes in the substrate are presented in this thesis. The objectives of this work consist of the following topics: (i) proposition of new antennas, including antennas with 3D printed substrates; (ii) proposal of antenna design, by means of adequate techniques of holes that result in the non-displacement of frequency, usually caused by change in the permittivity after insertion of the holes; (iii) proof that different geometric shapes of holes are not related to the variation of the resonance frequency; (iv) verifying that a nonconventional (non-cylindrical) geometry can promote efficiency improvements in design time; (v) application of an artificial neural network capable of improving the time to obtain return losses; (vi) proposition of low-cost techniques for the development of antennas with EBG substrate. The methodology of the research, theoretical reference and the analyze cited are presented throughout the work. The validations of the study proposals are presented through simulation results and prototype measurements.